ಉತ್ತರ ಕರ್ನಾಟಕದ ಪ್ರಸಿದ್ಧ ಗೀಗೀ ಮೇಳಗಳು - Ashoka Narode (Kannada Sahitya Parishattu, 2004)
This book gives us the information about the various fairs conducted by various commmunities of Uttara Kannada of Karnataka
Uttara karnatakada prasiddha geegee melagalu
Keywords: Kannada; ಉತ್ತರ ಕರ್ನಾಟಕದ ಪ್ರಸಿದ್ಧ ಗೀಗೀ ಮೇಳಗಳು; Uttara Karnatakada Prasiddha Geegee Melagalu; Folk Literature; Kannada; Kannada